Boron‐Functionalized Graphene Oxide‐Organic Frameworks for Highly Efficient CO2 Capture. Issue 3 (10th January 2017) - Haque, Enamul; Islam, Md. Monirul; Pourazadi, Ehsan; Sarkar, Shuranjan; Harris, Andrew T.; Minett, Andrew I.; Yanmaz, Ekrem; Alshehri, Saad M.; Ide, Yusuke; Wu, Kevin C.‐W.; Kaneti, Yusuf Valentino; Yamauchi, Yusuke; et al.
Abstract: The capture and storage of CO2 have been suggested as an effective strategy to reduce the global emissions of greenhouse gases. Hence, in recent years, many studies have been carried out to develop highly efficient materials for capturing CO2 . Until today, different types of porous materials, such as zeolites, porous carbons, N/B‐doped porous carbons or metal‐organic frameworks (MOFs), have been studied for CO2 capture. Herein, the CO2 capture performance of new hybrid materials, graphene‐organic frameworks (GOFs) is described. The GOFs were synthesized under mild conditions through a solvothermal process using graphene oxide (GO) as a starting material and benzene 1, 4‐diboronic acid as an organic linker. Interestingly, the obtained GOF shows a high surface area (506 m 2  g −1 ) which is around 11 times higher than that of GO (46 m 2  g −1 ), indicating that the organic modification on the GO surface is an effective way of preparing a porous structure using GO. Our synthetic approach is quite simple, facile, and fast, compared with many other approaches reported previously. The synthesized GOF exhibits a very large CO2 capacity of 4.95 mmol g −1 at 298 K (1 bar), which is higher those of other porous materials or carbon‐based materials, along with an excellent CO2 /N2 selectivity of 48.8. Abstract : CO2 is trapped ! The CO2 capture performance of new hybrid materials, graphene‐organic frameworks (GOFs), is described. The GOFs were synthesized under mild conditions through a solvothermal process using graphene oxide (GO) as a starting material and benzene 1, 4‐diboronic acid as an organic linker. The synthesized GOF exhibits a very large CO2 capacity of 4.95 mmol g −1, which is higher than of other porous materials or carbon‐based materials, and also shows an excellent CO2 /N2 selectivity of 48.8.